Analisis Kinerja Lalu Lintas Pada Ruas Jalan Jendral Sudirman Kabupaten Kuningan - Salsabila, Alfida; Hariani, Mira Lestira (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2024)
The traffic performance analysis research on this road section was carried out on Jalan Jendral Sudirman Kuningan Regency. The road has a high density. In connection with this, research is needed using the 1997 Indonesian Road Capacity Manual (MKJI) method. This research aims to analyze the performance of the Jendral Sudirman road section and provide technical recommendations that can be applied to the Jendral Sudirman road section. After conducting research at the observation location, the capacity value for peak hour is 2245.47 smp / hour, the degree of saturation is 0.70 (crowded smoothly), and the level of road service is included in the "C" category. For the next 5 years, the capacity value is 2245.47 smp / hour, the degree of saturation is 0.75 (dense creeping), the level of road service is included in the "D" category. For the next 10 years, the capacity value is 2245.47 smp / hour, the degree of saturation is 0.81 (creeping solid, the level of road service is included in the "D" category. Technical recommendations that can be applied are first, namely the reduction of side obstacles, the second technical recommendation is road widening, and the third technical recommendation is traffic engineering.  Keywords: Degree of Saturation, Side Obstacles, Road Section Performance, Road Level of Service.